Roles of Nrf2 in Gastric Cancer: Targeting for Therapeutic Strategies - Tahereh Farkhondeh; Ali Mohammad Pourbagher-Shahri; Mohsen Azimi-Nezhad; Fatemeh Forouzanfar; Aranka Brockmueller; Milad Ashrafizadeh; Marjan Talebi; Mehdi Shakibaei; Saeed Samarghandian (Molecules, 2021)
Nuclear Factor Erythroid 2-Related Factor 2 (Nrf2) is a specific transcription factor with potent effects on the regulation of antioxidant gene expression that modulates cell hemostasis under various conditions in tissues. However, the effects of Nrf2 on gastric cancer (GC) are not fully elucidated and understood. Evidence suggests that uncontrolled Nrf2 expression and activation has been observed more frequently in malignant tumors, including GC cells, which is then associated with increased antioxidant capacity, chemoresistance, and poor clinical prognosis. Moreover, Nrf2 inhibitors and the associated modulation of tumor cell redox balance have shown that Nrf2 also has beneficial effects on the therapy of various cancers, including GC. Based on previous findings on the important role of Nrf2 in GC therapy, it is of great interest to scientists in basic and clinical tumor research that Nrf2 can be active as both an oncogene and a tumor suppressor depending on different background situations.